Profitability Analysis In Indian Banking Sector - Dr. Deepika (International Journal of Advanced Science and Technology, 2020)
The term profitability is very helpful in providing a useful basis for measuring business efficiency and overall performance. B.B.Howod and M.Upton define profitability as the ability of an investment to earn return on its use. Thus profitability is a composite concept related to  the efficiency of an organization to earn profit. Gibson and Boyer defined “Profitability as  the ability of the firm to generate earning upon it ”. Franks and Broyles defines it with the help of capital market and opportunity cost; the expected return of  the capital markets is representing  the  opportunity cost. The capital market point to the companies against which to measure profitability In other words it’s a way in which profitable investment of a  project provides a return sufficient to attract capital from the capital market”